Meta-analyses describing the variables that influence the backfat, belly fat, and jowl fat iodine value of pork carcasses - J R Bergstrom; Michael D Tokach; Steven S Dritz; Terry A Houser; Jim L Nelssen; Robert D Goodband; Joel M DeRouchey (Kansas Agricultural Experiment Station Research Reports, 2010)
Concern about the quality of pork fat has increased in the United States over the last decade, largely because of the increased availability and use of dried distillers grains with solubles (DDGS) in swine diets. The iodine value (IV) of pork fat is commonly used as an indicator of quality. To identify the factors associated with carcass fat IV, meta-analyses were conducted to describe the relevant variables and to develop prediction equations to assist swine nutritionists and producers in producing pork fat with an acceptable IV. Data from 21 experiments were used to develop prediction equations for carcass fat IV of pigs fed a relatively constant dietary iodine value product (IVP) throughout the feeding period, and 6 experiments were used to develop prediction equations for carcass fat IV of pigs fed a dietary IVP-reduction strategy before marketing. Backfat, belly fat, and jowl fat IV were all highly correlated among the experiments that measured the IV of the multiple fat depots (r ≥0.880; P<0.001). As expected, the dietary concentrations of unsaturated (primarily polyunsaturated) fatty acids were the most important in predicting carcass fat IV. However, improved prediction models were achieved by including variables to describe the pigs' initial and final BW, ADG, and carcass leanness. Increased ADG, final BW, BW range over course of the diet, and backfat depth resulted in reduced backfat IV (P<0.02). Belly fat IV was also reduced with increasing final BW, BW range over course of the diet, and backfat depth (P<0.03). A reduced jowl fat IV was associated with an increase in backfat depth and a lower fat-free lean index (FFLI, P<0.02). Data analyzed to develop equations for predicting carcass fat IV using a dietary IVP-reduction strategy indicated that the concentrations of dietary polyunsaturated fatty acids in the initial diet were the most important. The concentrations of dietary polyunsaturated fatty acids in the reduced- IVP diet fed before marketing were also important in predicting the IV of carcass fat. However, the IV of backfat was the most amenable to change using an IVP-reduction strategy. Feeding the pigs for a longer period and to a heavier final BW resulted in a reduced backfat IV (P ≤ 0.05). These results indicate that, although primarily determined by dietary factors, an understanding of the other variables that influence the IV of pork fat is necessary to reduce the likelihood of concerns with pork fat quality.; Swine Day, Manhattan, KS, November 18, 2010
Keywords: Swine Day; 2010; Kansas Agricultural Experiment Station contribution; no. 11-016-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1038; Swine; Fat quality; Fatty acids; Iodine value; Prediction equation